Description Of Bag Load With Antropometry Of Elementary School Students - Krishna Moorthi, Priya Darshini; Machrina, Yetty; Laksmi, Lidya Imelda; Yaznil, Muhammad Rizki (Sumatera Medical Journal, 2020)
Background. Low back pain is one of the most common health problem among school students. Carrying heavy backpack to school is one of the cause of low back pain. Objectives. To identify the bag load carried by the students and antropometry of the students. Method. This research is a descriptive observasional with cross sectional method. Data used is a primer data which is from 268 students by measuring their body weight, height, bag weight and also by interviewing them using interview guidelines. Results. The results obtained from 268 elememtary school students of Siti Hajar mostly have normal nutritional status. The average bag weight at level I (6.071%), level II (8.510%) and level III (10.812%) where the majority of bag loads compared to elementary school antropometry were included in the mild category 47.6% at level I, 74.7% at level II and 84.3% at level III eventhough there were some children in the heavy category. 88.8% of children carry their school bags using two shoulders, with a duration of time <30 minutes (61.7%). Respondents who experienced back pain (4.9%) and who did not experience back pain (95.1%). Conclusions. The weight of Siti Hajar Elementary School children bag against antropometry has not exceeded the recommended load limit. Key words. Bag load, antropometry, cross-sectional, interview